Successful Biological Treatment of Cutaneous wound Healing with Comparation of Aqueous Humour Fluid and Fat Graft; Cattle as Model - Qayes Taref Ali; Muslem Fahim Diwan; Amir I. Towfik (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aqueous humour fluid and fat graft effect on wound healing by containing growth factors. Aim of this studyto evaluate the benfit effect of aqueous humour fluid and fat graft in wound healing in cattle. Twenty sevenadult female local breed randomly divided into 3 equal groups. G1 have been treated by aqueous fluid, G2treated with fat graft, while the last group ( control group ) leaft without treatment. In conclusion fat grafttreated group appear better healing during study period compare with other groups.